Effect Of Salicylic Acid On Biochemical (Disease Resistant) Compounds In Brassica Juncea Rlm619 (Applied Biological Research, 2013)
Salicylic acid (SA) is a well known inducer of systemic acquired resistance  (SAR) in several plants. In present study the ability of SA to induce resistance  in Indian mustard (Brassica juncea) RLM619 was investigated. SA (10 and 50  ppm) treated seeds of B. juncea, germinated in petri-plates, showed maximum  of 34.0, 21.7 and 28.5% increase in defense-related enzyme activities viz., peroxidase (PO), phenylalanine ammonia lyase (PAL) and superoxide  dismutase (SOD) in hypocotyls, respectively, as compared to water-treated  control. Similar trend was observed in cotyledonary leaves of germinated  seedlings. Corresponding changes in phenolic contents was also observed. SA  treatment @ 50 ppm showed maximum increase in defense enzymes and  phenolics on all the days of observation, except for SOD activity where a  decrease was seen on 3rd day. Qualitative profiling of phenolics showed that  SA treatment enhanced the number of phenolic compounds as compared to  control. It may be inferred that SA promotes resistance in mustard by  enhancing the level of defense-related compounds and can be exploited to  limit fungicidal use through induction of elevated levels of natural resistance.
Keywords: Brassica juncea; defense enzymes; salicylic acid; systemic acquired resistance